Cathcart Castle, Glasgow – Excavations 1980–81. (October 2016) - Kerr, Brian; Cox, Adrian; Gallagher, Dennis; Graves, Pamela; Haggarty, George; Hall, Derek; Malden, Eileen; Malden, John; Smith, Catherine; Stell, Geoffrey; Munro, David; Fyles, Chris; et al.
Abstract : Excavations on the site of the tower-house at Cathcart, demolished in 1980, produced evidence for the construction of the tower and associated barmkin, dated to the mid 15th century. No earlier structural remains were found but residual pottery suggests that the site was occupied prior to the construction of the tower. The interior of the tower was remodeled in circa 1630–40 in brickwork, an early dated example of the use of this material in Scotland, and decorated with elaborate plasterwork. The barmkin was dismantled and a new range of buildings added, also in the 17th century. Significant finds included an important clearance assemblage of local and imported ceramics, ironwork and glass from the partial demolition of the castle in the mid 18th century, deposited with assemblages of 17 th -century plasterwork.